Proceedings of the 2019 CHI Conference on Human Factors in Computing Systems 2019
DOI: 10.1145/3290605.3300622
|View full text |Cite
|
Sign up to set email alerts
|

Why Do You Need This?

Abstract: Recent scandals involving data from participatory research have contributed to broader public concern about online privacy. Such concerns might make people more reluctant to participate in research that asks them to volunteer personal data, compromising many researchers' data collection. We tested several motivational messages that encouraged participation in a citizen science project. We measured people's willingness to disclose personal information. While participants were less likely to share sensitive data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…A number of papers have empirically demonstrated that certain design features, such as variety of customization options [34], high immediacy levels [35], perception of information control [34,36], exposure to calls of action [37], videos including female narrators combined with vibrant colors and light musical tones [38], a dynamic privacy score [39], norm-shaping design patterns [40], as well as contextual cues amplifying or downplaying privacy concerns [41], can increase the disclosure of personal information. Also, studies have shown that persuasive messages that are more positively framed or include higher argument strength [42] as well as motivational messages can increase the disclosure of personal sensitive information [43]; while initially participants reacted Compensation of different types, trust (excerpt) Participants did not claim to be more willing to provide information in the presence of incentives, but in fact, as indicated by their behavior, were more inclined to do so.…”
Section: Plos Onementioning
confidence: 99%
“…A number of papers have empirically demonstrated that certain design features, such as variety of customization options [34], high immediacy levels [35], perception of information control [34,36], exposure to calls of action [37], videos including female narrators combined with vibrant colors and light musical tones [38], a dynamic privacy score [39], norm-shaping design patterns [40], as well as contextual cues amplifying or downplaying privacy concerns [41], can increase the disclosure of personal information. Also, studies have shown that persuasive messages that are more positively framed or include higher argument strength [42] as well as motivational messages can increase the disclosure of personal sensitive information [43]; while initially participants reacted Compensation of different types, trust (excerpt) Participants did not claim to be more willing to provide information in the presence of incentives, but in fact, as indicated by their behavior, were more inclined to do so.…”
Section: Plos Onementioning
confidence: 99%
“…Another barrier to participation is that willingness to share data depends strongly on the data type [ 32 , 47 , 67 ], even though there are divergent findings in the literature about which data types people feel most uncomfortable sharing [ 37 , 38 , 42 , 61 - 65 ]. For example, previous studies with young adults have observed a high willingness to donate DNA samples [ 33 , 34 ], but 2 extensive worldwide surveys have observed the opposite [ 36 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Questions in this group concerned how comfortable or uncomfortable participants would feel about sharing different deidentified data sources for a research repository, as previous studies have shown that willingness to share personal health data varies according to the data source [ 61 - 63 ]. Data sources were grouped as (1) biospecimen samples and input data provided through health questionnaires (online or in-person); and (2) passive data collected through smartphone or wearable devices, without end user input.…”
Section: Methodsmentioning
confidence: 99%
“…Questions in this group concerned how comfortable or uncomfortable participants would feel about sharing different deidentified data sources for a research repository, as previous studies have shown that willingness to share personal health data varies according to the data source [61][62][63]. Data sources were grouped as (1) biospecimen samples and input data provided through health questionnaires (online or in-person); and (2) passive data collected through smartphone or wearable devices, without end user input.…”
Section: Willingness To Share Datamentioning
confidence: 99%